Military Civil Relations in Singapore, Malaysia, Thailand, Vietnam, America, China, Turkey and Egypt - Maulana, Arman; Rosmayati, Siti (Yayasan Azka Hafidz Maulana, 2024)
This article analyzes civil-military relations in Singapore, Malaysia, Thailand, Vietnam, the United States, China, Turkey, and Egypt. Each country has a unique approach to managing the role and influence of the military in government. Singapore and Malaysia emphasize civil supremacy and close coordination. Thailand and Türkiye have a history of military coups that influenced national politics. Vietnam and China demonstrate communist party control over the military. The United States upholds the principle of civilian control, while Egypt continues to face military interference in politics. This study highlights the importance of striking a balance between civilian control and military effectiveness to maintain national stability.